P3SPS pada Program Talk Show Mata Najwa Episode PSSI Bisa Apa Jilid 6: Lagi-Lagi Begini - Anggraini, Ayu Dwi; Hartanto, Denny Antyo; Kartika, Bambang Aris (ROLLING, 2024)
Television has a significant influence in shaping public opinion and mindset. Research in 2021 found some programs didn't meet KPI standards. "Mata Najwa" episode "PSSI Bisa Apa Jilid 6: Lagi-lagi Begini" on Trans7 sparked controversy and legal action from PSSI representative. The purpose of this research is to examine the alignment of the content of the talk show program "Mata Najwa" episode "PSSI Bisa Apa Jilid 6: Lagi-Lagi Begini" with the P3SPS. This research utilized Tzvetan Todorov's narrative structure theory, modified by Nick Lacey, as the primary theory, and the Pedoman Perilaku Penyiaran dan Standar Program Siaran to assess the conformity of the narrative with the broadcasting norms. The research employed a qualitative research design with a descriptive writing technique. The data collection techniques used are observation and literature review. The data analysis stage includes data reduction, data presentation, and drawing conclusions. The research findings conclude that the conformity of the content of the talk show "Mata Najwa" episode " PSSI Bisa Apa Jilid 6: Lagi-lagi Begini" with the Pedoman Perilaku Penyiaran dan Standar Program Siaran is appropriate, and the broadcast did not violate the guidelines.